Corporate Social Responsibility and Employees Commitment in Nepalese Organization - Niroula, Ballav; Panthi, Top Lal (Cognition, 2021)
The effect of corporate social responsibility on employee commitment in Nepalese service and manufacturing sectors is investigated in this study. The primary sources of evidence were used to determine the respondents' views on the various impacts of corporate social responsibility. A total of 280 respondents took part in the survey. The findings were tested using a descriptive and analytical research design. A standardized questionnaire has been prepared to achieve the study's aim. The meaning and effect factors was tested using correlation coefficients and regression models. The findings suggest that corporate social responsibility and employee engagement have a strong and meaningful relationship. This study concludes that increase in components of corporate social responsibility leads to increase in employee commitment in the organization.